Development of E-Learning Based Human Resource Management Assisted by Edlink on The Quality Of Elementary School Teachers - Kurniawan, Romi; Gistituati, Nurhizrah; Hadiyanto, Hadiyanto (Mudir : Jurnal Manajemen Pendidikan, 2023)
This research was conducted to develop human resource management based on e-learning using the Edlink platform and evaluate its effectiveness on the quality of elementary school teachers. In this study, the Research and Development (R&D) method with 4 stages (4D) was used. Expert validation results show that this development is very feasible with a feasibility validation percentage of 91.67%, practicality of 92%, and effectiveness of 89.5%. The teacher's response to this development was very positive with a percentage of 87.9%, indicating that the development of HR management based on e-learning assisted by Edlink is very appropriate to use as an effort to improve the quality of teachers in online learning. It can be concluded that this development is effectively and practically used as a learning medium to improve the quality of teachers in schools, especially in the current online learning context.